Interventional effect of ACT on social interaction in children aged 7-10 years with Asperger syndrome - HUANG Jin, YUAN Bin, ZHAO Shan, HU Maorong (Xin yixue)
Objective To evaluate the effect of acceptance and commitment therapy （ACT） on the psychological intervention of Asperger syndrome children aged 7-10 years. Methods A total of 60 Asperger syndrome children admitted to the Third Hospital of Fuzhou from January 1， 2023 to December 31， 2023 were enrolled and divided into the ACT （n = 30） and control groups （n = 30） using the random number table method. Children in the control group were given with health psychological education， and those in the ACT group received ACT on the basis of health psychological education. All children were investigated by using Aberrant Behavior Checklist （ABC）， Screen for Child Anxiety Related Emotional Disorders （SCARED）， Self-Rating Scale Depressive Disorder in Childhood （DSRSC）， Acceptance and Action Questionnaire-2nd Edition （AAQ-Ⅱ）， Cognitive Fusion Questionnaire-Fusion （CFQ-F）， General Self-Efficacy Scale （GSES） before and after corresponding interventions and on-the-spot assessment. Results After interventions， the scores of ABC， DSRSC， SCARED， AAQ-Ⅱ and CFQ-F in the ACT group were lower than those before interventions and those in the control group after intervention， while the GSES score in the ACT group was higher than that before interventions and that in the control group after interventions， and the differences were statistically significant （all P < 0.05）. In the control group， no statistical significance was found in the scores of ABC， DSRSC， SCARED， GSES， AAQ-Ⅱ and CFQ-F before and after interventions （all P > 0.05）. The social interaction， verbal ability and total scores after intervention were lower than those before intervention in the ACT group （all P < 0.05）. In the ACT group， there was a negative correlation between self-efficiency score of GSES with DSRSC and SCARED scores （both P < 0.05）， and the experiential avoidance and cognitive fusion scores of AAQ-Ⅱ were positively correlated with the ABC scores （both P < 0.05）. Conclusions ACT can improve the psychological resilience of Asperger syndrome children aged 7-10 years， enhance their ability to deal with various stresses in life， alleviate the degree of experiential avoidance and cognitive integration and improve their social skills， which yields better overall effect than routine psychological health education.